“Segmental Necrotizing Granulomatous Neuritis”: A Rare Manifestation of Hansen Disease—Report of 2 Cases - P. S. Jayalakshmy; P. H. Prasad; V. V. Kamala; R. Aswathy; Priya Pratap (Case Reports in Dermatological Medicine)
Segmental necrotizing granulomatous neuritis (SNGN) is a rare condition affecting the nerves of Hansen disease patients. This is usually seen as a complication in association with the skin lesions of Hansen disease. Though very rare, it can also be the first presenting symptom of pure neuritic leprosy. We hereby report 2 cases of SNGN—one case of pure neuritic leprosy with initial presentation as SNGN and another, a treated case of borderline tuberculoid leprosy which relapsed with skin lesions and associated SNGN in the peripheral nerve.